Limited health insurance coverage amidst upsurge of non-communicable diseases in Uganda - Mpuuga, Dablin; Mbowa, Swaibu; Odokonyero, Tonny (Economic Policy Research Centre, 2019)
This brief uses the 2016/17 Uganda National Household Survey (UNHS) and the World Development Indicators (WDI) to show the extent of health insurance coverage for non-communicable diseases (NCDs) such as diabetes, high blood pressure and heart diseases among others. Results indicate that: (i) NDCs affect people of all socio-economic groups; (ii) more Ugandans suffering from NCDs are willing to pay for health insurance, but very few are holders of insurance policies in this regard; (iii) other diseases like malaria are more easily insured compared to NCDs, an indication that the providers of health insurance services are not keen to insure sufferers of NCDs; (iv) there are regional differences in health insurance coverage as well as prevalence of NCDs, with the burden of NCDs more intense in the Bukedi, Busoga and Teso sub-regions, whereas NCDs are least prevalent in Kigezi and Ankole sub-regionsand (v) NCDs are likely to erode gains in poverty reduction at household level, because it is equally high among poor households with the least capacity to afford health insurance. We there by, recommend establishing special screening centres for NCDs in public health facilities especially health center II’s and III’s. This will promote early detection and early treatment hence curbing expensive costs for treating severe and chronic NCDs. Preventive measures need to be emphasized as well. These include regular body exercises and monitored nutrition which all lower the risk of NCDs. We further suggest incorporating and prioritizing NCDs into the proposed national health insurance scheme.